Chryseobacterium lacus sp. nov. Isolated From the Surface Water of Two Lakes With Light-Induced Carotenoid Production - Zhang, Jing; Gao, Cheng; Yu, Xue-Mei; Lun, He-Yuan; Du, Zong-Jun (Frontiers in Microbiology, 2020)
Two Gram-stain-negative, rod-shaped, gliding, catalase-positive, and facultative anaerobic, strains YLOS41T and XH07, were isolated from surface water of Yilong Lake and West Lake of Dali in Yunnan Province, respectively. Both strains were yellow-colored under light conditions and white-colored under dark conditions. The results of physiological and chemotaxonomic characterization, sequencing and phylogenetic analysis, and draft genome sequence comparison demonstrated that the two strains represented a single novel species within the genus Chryseobacterium, for which the name Chryseobacterium lacus sp. nov., is proposed. The type strain is YLOS41T (=KCTC 62352T= MCCC 1H00300T), and the second strain is XH07 (=KCTC 62993). During the cultivatoin process, we found that the colony color of the two strains changed from white to yellow with illumination. The study investigated the effects of light irradiation on the strain YLOS41T. Results showed that light irradiation did not affect the growth of cells but significantly increased carotenoid synthesis, which caused the change of colony color. In-depth metabolic analysis was conducted by transcriptome. The predominant changes were found for genes involved in carotenoid synthesis as protection from light damage. Based on the genome and transcriptome, we proved that strain YLOS41T possessed a complete synthetic pathway of carotenoid, and speculated that the production was zeaxanthin. This was the first report of Chryseobacterium species with light-induced carotenoid synthesis. This study enhances our present knowledge on how Chryseobacterium species isolated from surface water responds to light damage.